Efficacy Analysis of Combining Sintilimab with Neoadjuvant Chemotherapy in Treating Middle and Advanced Rectal Cancer Based on Big Data. (16th September 2022) - Wang, Yifei; Fei, Jiandong; Zheng, Yanan; Li, Ping; Ren, Xiaodong; An, Yongzhu
Abstract : Objective . To analyze the efficacy of combining sintilimab with neoadjuvant chemotherapy in treating middle and advanced rectal cancer based on big data. Methods . According to the inclusion and exclusion criteria, 43 patients with middle and advanced rectal cancer, who were treated with sintilimab and neoadjuvant chemotherapy in General Surgery of the hospitals of Zhangjiakou city from January 2020 to January 2022, were selected for the retrospective study. The patients' short-term efficacy was scientifically evaluated, and the factors affecting efficacy and the correlation were analyzed. Results . Among the 43 enrolled patients, 30 of them had regional lymphatic metastasis but none had distant metastasis; most patients were at Broders II and TNM III, and all of them had adenocarcinoma; the total response rate was 69.77% (30 cases), with no grade IV and V adverse reactions; the patients were divided into the effective group and the ineffective group after treatment based on the evaluation results of short-term efficacy, and analysis of the relevant factors exposed in both groups revealed significant differences in age, tumor size, CEA, NLR value, PLR value, TNM stage, and presence of combined lymphatic metastasis between the two groups (P < 0.05 ); univariate analysis showed that tumor size, CEA, TNM stage, and combined lymphatic metastasis were the independent risk factors affecting the efficacy in patients with middle to advanced rectal cancer (P < 0.05 ); and through the Spearman correlation analysis of the above independent risk factors, it was further confirmed that tumor size, CEA, TNM stage, and combined lymphatic metastasis were negatively correlative with the efficacy of combining sintilimab with neoadjuvant chemotherapy in treating middle to advanced rectal cancer (P < 0.05 ). Conclusion . Combining sintilimab with neoadjuvant chemotherapy has good efficacy and safety profile, which is conducive to subsequent surgery; in contrast, larger tumor diameter, higher CEA level, higher TNM stage, and more serious lymphatic metastasis are all independent risk factors affecting treatment sensitivity and can lead to poor efficacy.